Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.7759/cureus.3881
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Pneumomediastinum and Pneumoperitoneum with Concurrent Massive Subcutaneous Emphysema due to Repositioning of a Tracheostomy Tube

Abstract: Tracheostomy is a common procedure seen in critically ill patients that require long term ventilatory support. As with all airway access procedures, tracheotomy with prolonged tracheal tube placement comes with possible risks such as tracheal scarring, tracheal rupture, pneumothorax, tracheoesophageal fistula among others. Another possible complication, though rare, is escape of free air into the surrounding tissue, as well as pneumomediastinum (PM). This may occur due to various reasons, some of them being tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Deja et al [12] found that conservative management was preferred for patients who did not require mechanical ventilation and when their emphysema was only mild and stable during ventilation. Studies recommend that surgery is pursued for patients with posterior tracheal wall perforations greater than 2 cm and mainly depends on how proximal[ the injury is to the carina [14] . However, conservative treatment can still be managed in cases where there was no history of pulmonary or mediastinal surgery, as in our patient who underwent debridement for her right shoulder, and is increasingly becoming the mainstay of therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deja et al [12] found that conservative management was preferred for patients who did not require mechanical ventilation and when their emphysema was only mild and stable during ventilation. Studies recommend that surgery is pursued for patients with posterior tracheal wall perforations greater than 2 cm and mainly depends on how proximal[ the injury is to the carina [14] . However, conservative treatment can still be managed in cases where there was no history of pulmonary or mediastinal surgery, as in our patient who underwent debridement for her right shoulder, and is increasingly becoming the mainstay of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, conservative treatment can still be managed in cases where there was no history of pulmonary or mediastinal surgery, as in our patient who underwent debridement for her right shoulder, and is increasingly becoming the mainstay of therapy. A high concentration of oxygen is helpful for subcutaneous emphysema, and some cases have shown that 2-3 cm blowhole incisions in the supraclavicular or infraclavicular region are helpful for releasing subcutaneous air [14] . Other cases have shown that subcutaneous drains are successful at significantly reducing subcutaneous air and can be one of the methods implemented [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The air within the abdominal cavity may also lead to the development of air emboli via the introduction of air into the abdominal blood vessels or organs, possibly causing neurological damage or cardiovascular collapse [4]. Pneumomediastinum, pneumopericardium, and pneumoperitoneum may also occur in some scenarios as the fascia allows the passage of air between cavities [5][6][7]. No cases of intentional body insufflation have been documented in the literature to date.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumoperitoneum is characterized by the presence of abnormal gas (as air) in the potential abdominal space [1]. This usually is considered a surgical emergency and is associated with perforated abdominal viscus in more than 90% of cases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%